Therapeutic strategies of thromboembolic events in patients with inflammatory bowel diseases: Two case reports. Issue 9 (March 2019) - Zhu, Lei; Cheng, Jiafei; Gu, Peiqing; Liu, Yajun; Liu, Junlou; Wang, Jianhua; Shen, Hong
Abstract: Rationale: Inflammatory bowel disease (IBD), including Crohn disease (CD) and ulcerative colitis (UC), is characterized by chronic inflammatory condition and immunological abnormalities, which probably develop into venous thromboembolic events (VTEs). VTE in IBD patients mostly occurs at deep venous thrombosis (DVT) and pulmonary embolism (PE). The complications are extremely important in clinical practice considering the high mortality rate. Hence, an early diagnosis of IBD and the control of complications play an important role in therapy of thromboembolic events (TEEs). Patient concerns: Case 1 was a 31-year-old man with chronic UC who presented with signs of thromboembolism. Case 2 was a 43-year-old woman with CD complicated by fistulas. Diagnoses: Computed tomography (CT) and digital subtraction angiography (DSA) of the patient (case 1) suggested a thrombus in cerebral vein. The patient (case 2) developed acute ischemia of her right arm; B ultrasonography revealed a thrombus in the distal of the right subclavian artery accompanied by stenosis. Interventions: To lower blood viscosity and overcome the risk of deep thrombosis, the patient (case 1) was treated with a combination of low-molecular-weight heparin and dextran as anticoagulation. For the patient (case 2), anticoagulation treatment with 75 mg qd clopidogrel (plavix) and 1.25 mg qd warfarin was performed. Outcomes: In both patients, no further TEE occurred during follow-up 1 year and one and a half years, respectively. Lessons: It is important to pay attention to IBD patients especially those with high coagulation state.